Social Work Intervention for the Empowerment of Transgender Community in Kerala, India - Antony, Popson; Johny, John Colins (Journal of Social Work Education and Practice, 2017)
Transgender is a term that not yet got much attention in our society. Various kinds of discrimination faced by transgender community are suppressed due to lack of awareness and knowledge. This article attempts to view the needs of the transgender community from the perspective of Maslow’s hierarchy of needs theory. He used the terms ‘physiological, safety, belongingness and love, esteem, self-actualization and self-transcendence’ to describe the pattern of human development. This article tries to explain the limitations in transgender person’s holistic development and harmonious functioning in the society. Article also put forward the suggestions on how to reintegrate transgender community and also points out how it will contribute towards the development of entire society.
Keywords: Transgender; Needs; Social Work Intervention; Empowerment; Holistic Development